Działania promocyjne kościelnych bibliotek naukowych na przykładzie Biblioteki Teologicznej Uniwersytetu Śląskiego w Katowicach - Muc, Agata (Archiwa, Biblioteki i Muzea Kościelne, 2012)
Promotional activities undertaken by the Theological Library at University of Silesia are primarily aimed at informing people about the content of the accumulated books and the offer of services. This goal is achieved by using, appropriately selected and adapted to the needs of the church academic library, promotional tools such as the exhibition advertising, public relations and personal promotion. What proved particularly helpful in creating a positive image of the institution was systematic exhibition advertising, educational and publishing activities, as well as maintaining contact with people through establishing cooperation with various research institutions and associations.